Peran takut akan kebahagiaan terhadap kesehatan mental masyarakat Indonesia berdasarkan konsep dua kontinuum kesehatan mental - Najib, Asalia; Kumalasari, Asteria Devy; Abidin, Zainal (Jurnal Psikologi Ulayat, 2025)
Fear of happiness is the belief that there may be negative consequences associated with experiencing happiness. This belief is speculated to lead individuals to avoid positive emotions, ultimately contributing to diminished levels of mental health, encompassing both psychological functioning and psychological dysfunction. The objective of this study was to investigate the impact of fear of happiness on mental health using dual continua, encompassing psychological functioning as a continuum of mental health and psychological dysfunction as a continuum of mental illness within the Indonesian population. Using non-probability sampling technique with convenience sampling type and distributing it via social media, the total sample consisted of 1720 Indonesian citizens. The findings indicated that fear of happiness significantly negatively influences the continuum of mental health and positively contributes to the continuum of mental illness among the Indonesian population. Furthermore, variations in fear of happiness scores were observed across different mental health categories, with the highest scores found in the floundering category and the lowest in the flourishing categorization.